2017
DOI: 10.1186/s12889-017-4635-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent alcohol use and parental and adolescent socioeconomic position in six European cities

Abstract: BackgroundMany risk behaviours in adolescence are socially patterned. However, it is unclear to what extent socioeconomic position (SEP) influences adolescent drinking in various parts of Europe. We examined how alcohol consumption is associated with parental SEP and adolescents’ own SEP among students aged 14–17 years.MethodsCross-sectional data were collected in the 2013 SILNE study. Participants were 8705 students aged 14–17 years from 6 European cities. The dependent variable was weekly binge drinking. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 48 publications
(61 reference statements)
7
37
1
5
Order By: Relevance
“…Others similarly reported that accommodation with parents during the semester was negatively associated with high frequency of drinking, heavy episodic drinking, and problem drinking [7]. Our observation that parental education was associated with one alcohol behavior supports other research, where adolescent drinking was associated with adolescents' own but not with parental socioeconomic position [49]. Others found no relationships between alcohol consumption variables and various combinations of parental educational [7].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Others similarly reported that accommodation with parents during the semester was negatively associated with high frequency of drinking, heavy episodic drinking, and problem drinking [7]. Our observation that parental education was associated with one alcohol behavior supports other research, where adolescent drinking was associated with adolescents' own but not with parental socioeconomic position [49]. Others found no relationships between alcohol consumption variables and various combinations of parental educational [7].…”
Section: Discussionsupporting
confidence: 84%
“…Very few studies assessed alcohol consumption behaviors and/or academic performance among university students in Finland. Segregated studies examined some variables in isolation, younger or older age groups, or did not include academic performance, [49][50][51]; included one type of alcohol consumption behavior among medical students only [52]; or were outdated [53]. This is despite that the levels of alcohol consumption in Finland, although close to the OECD average, have increased over the last 30 years [54]; and the prevalence of HED in 2016 among those aged 15-19 years in the population was 31.9% and among drinkers only of the same age was 51.6% [55].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding age, our findings are consistent with those of other studies [45][46][47][48] that show that alcohol use, as well as the use of other drugs, increases with age. Moreover, this study showed an association between availability of money and excessive alcohol use, finding that as weekly pocket money increases, so does the likelihood of consuming alcohol.…”
Section: Discussionsupporting
confidence: 92%
“…Despite that "Scandinavian snus" has become the most commonly used tobacco among Norwegian youth [22] and that little difference in "snus" consumption has been observed among adults in terms of education level [23], no other study has, to the best of our knowledge, reported risk of using smokeless tobacco among NEET youth compared to their high school peers. Other studies examining substance use among adolescents have shown that adolescents' drinking habits were related to their own, but not their parents' socioeconomic position [24], and that having high academic goals, such as planning to graduate from university, was identified as a strong protective factor for cannabis, alcohol and tobacco use in adolescence [25]. A cross-sectional study has also indicated that psychosocial factors, such as the inability to control life and emotional isolation, may be plausible mediators for the relationship between unemployment and smoking in Italian adults [26].…”
Section: Discussionmentioning
confidence: 94%